New species of gall fly (Diptera: Fergusoninidae) from Eucalyptus camaldulensis (Myrtaceae) in southern Australia and its associated parasitoids and inquilines - Taylor, Gary S.; Hyder, Brittany K.; Davies, Kerrie A. (Zootaxa, 2019)
A new species of gall fly, Fergusonina nodulosa sp. nov. (Diptera: Fergusoninidae) is described from Eucalyptus camaldulensis Dehnh. (Myrtaceae) in southern Australia. The adult fly is yellow with dark brown to black markings, the male postgonites have one large distal tooth and an ovoid subapical lobe with two lateral setae, the female postabdomen is short and sparsely setose, and the wing has a posterior cross vein. The larva possesses a dorsal shield comprising rows of raised spicules on thoracic segments 1–3 and abdominal segments 1–7, and the puparium is heavily sclerotised dark brown, barrel-shaped, bearing the dorsal shield. Fergusonina nodulosa sp. nov. forms nodular ‘stem’ galls initiating from the axial shoot buds. The galls are 2–8 mm in diameter with an average volume of 123 (range 25–480) mm3. Thirteen species of Hymenoptera, comprising primary parasitoids and hyperparasitoids of the gall fly and associated lepidopteran inquilines, and three species of Lepidoptera inquilines were reared from galls of this new species. Fergusonina nodulosa sp. nov. is associated with the obligate mutualist nematode, Fergusobia camaldulensae Davies.